2021
DOI: 10.1159/000519910
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Precise Application of Bioadhesives to Prevent IPPROM on a Pregnant Sheep Model

Abstract: <b><i>Introduction:</i></b> Iatrogenic preterm premature rupture of the membrane remains the Achille’s heel of fetoscopy. The aim of this study was to show in vivo feasibility of fetal membrane (FM) defect sealing by the application of tissue glues with umbrella-shaped receptors. <b><i>Methods:</i></b> First, we adapted our previously described ex vivo strategy and evaluated the adhesion strength of different tissue glues, Histoacryl® and Glubran2®, by bonding po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…77 Unfortunately, the use of this glue caused compression, contraction and crush artifact of the chorion. Other glues such as the cyanoacrylates Dermabond and Histoacryl have been shown to greatly glue to the FMs, 81 but they increased apoptosis and caused epithelial cell disruption when tested ex vivo. 78 Furthermore, cyanoacrylates have been reported to show non-elastic adhesion to tissues, 82 which increases the risk of tissue damage due to traction.…”
Section: Ex Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…77 Unfortunately, the use of this glue caused compression, contraction and crush artifact of the chorion. Other glues such as the cyanoacrylates Dermabond and Histoacryl have been shown to greatly glue to the FMs, 81 but they increased apoptosis and caused epithelial cell disruption when tested ex vivo. 78 Furthermore, cyanoacrylates have been reported to show non-elastic adhesion to tissues, 82 which increases the risk of tissue damage due to traction.…”
Section: Ex Vivo Studiesmentioning
confidence: 99%
“…9B), but FM integrity was not examined. Recently, several cyanoacrylates with the support of a PTFE-coated nitinol receptor 81,111 (Fig. 9C) and integrated semirigid bioadhesive patches 90 (Fig.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Next, to evaluate the in vivo biocompatibility, stability, and FM sealing capacity of the elastic MG, we adapted our earlier described sheep model for the closure of FM defects with sealing patches [26].…”
Section: Ewe and Fetal Performancementioning
confidence: 99%
“…In the last years, approaches have been developed to apply commercially available glues (cyanoacrylates) [[21], [22]] or methylcellulose-based patches [[23]] to seal the FM defect. Those studies reported a 100% fetal survival, but the use of cyanoacrylates seemed to prevent AF leakage to a higher extent [[22]].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, approaches have been developed to apply commercially available glues (cyanoacrylates) [[21], [22]] or methylcellulose-based patches [[23]] to seal the FM defect. Those studies reported a 100% fetal survival, but the use of cyanoacrylates seemed to prevent AF leakage to a higher extent [[22]]. This particular sealing approach is based on an umbrella-shaped receptor made of the shape-memory alloy nitinol coated with polytetrafluoroethylene.…”
Section: Introductionmentioning
confidence: 99%